PENGARUH HEDONIC SHOPPING MOTIVES DAN PROMOTION TERHADAP IMPULSE BUYING (Studi pada Mahasiswa UMSurabaya Yang Menjadi Konsumen Shopee) - Mochammad Faisal; Muhammad Anang Firmansyah; Asyidatur Rosmaniar; Ali Imaduddin Futuwwah (PROCEEDING UMSURABAYA, 2022)
Modern consumers tend to make unplanned purchases coupled with advances in technology and the flow of information that makes online shopping easier. Shopee is one of the well-known marketplaces and is widely used by the public. This study aims to determine the effect of hedonic shopping motives and promotions on impulse buying at UMSurabaya students who become Shopee consumers. There are three hypotheses tested, namely 1. Hedonic Shopping Motives have a positive and significant effect on Impulse Buying. 2. Promotion has a positive and significant effect on Impulse Buying. 3. Hedonic Shopping Motives and Promotions positively and significantly affect Impulse Buying. To determine the sample in this study, Cluster Sampling was used with the criteria of UMSurabaya students, Faculty of Economics and Business, Management Study Program, class of 2017 – 2019 who became Shopee consumers. This study used a sample size of 100 respondents using a questionnaire. This study uses the quantitative method and is processed with SPSS ver 25. This study reveals that hedonic shopping motives have a positive and significant influence on Impulse Buying in UMSurabaya students who become Shopee consumers. In contrast, promotions do not have a positive and significant effect on impulse buying on UMSurabaya students who Become Shopee consumers.    Keywords: Hedonic Shopping Motives; Promotion; Impulse Buying.